2017
DOI: 10.5194/acp-17-2009-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sources and atmospheric processing of winter aerosols in Seoul, Korea: insights from real-time measurements using a high-resolution aerosol mass spectrometer

Abstract: Abstract. Highly time-resolved chemical characterization of nonrefractory submicrometer particulate matter (NR-PM1) was conducted in Seoul, the capital and largest metropolis of Korea, using an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS). The measurements were performed during winter, when elevated particulate matter (PM) pollution events are often observed. This is the first time that detailed real-time aerosol measurement results have been reported from Seoul, Korea, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 100 publications
7
68
2
Order By: Relevance
“…The PM 1 composition over Seoul is dominated by pNO 3 and SOA, similar to what was observed on the ground during the same time period (Kim et al, 2018). The composition over Seoul is more similar to what has been observed over Mexico City during MILAGRO (DeCarlo et al, 2008) and in Los Angeles during CalNex (Hayes et al, 2013) than observed over large urban areas in Asia (Hu et al, 2016).…”
Section: Pm 1 Concentration and Composition Over South Korea During Ksupporting
confidence: 81%
See 2 more Smart Citations
“…The PM 1 composition over Seoul is dominated by pNO 3 and SOA, similar to what was observed on the ground during the same time period (Kim et al, 2018). The composition over Seoul is more similar to what has been observed over Mexico City during MILAGRO (DeCarlo et al, 2008) and in Los Angeles during CalNex (Hayes et al, 2013) than observed over large urban areas in Asia (Hu et al, 2016).…”
Section: Pm 1 Concentration and Composition Over South Korea During Ksupporting
confidence: 81%
“…The slope over Seoul (−0.69) is close to the average slope for numerous studies summarized by Chen et al (2015) (−0.60) and similar to the range of slopes (−0.7 to −1.0) for studies impacted by urban pollution (Aiken et al, 2009;Docherty et al, 2011;Ge et al, 2012), including Los Angeles during Cal-Nex (ranges from −0.64 to −0.68 from Hayes et al, 2013, and or chamber studies investigating the photooxidation of combustion exhausts (Heald et al, 2010;Lambe et al, 2012;Jathar et al, 2013;Presto et al, 2014;Liu et al, 2015). This generally indicates that the photochemistry controlling the production of SOA is similar in urban areas, including photooxidation of diesel and gasoline emissions, evaporative diesel and gasoline, and cooking emissions (Hayes et al, 2015;Woody et al, 2016;Janssen et al, 2017;Ma et al, 2017;Kim et al, 2018).…”
Section: Oxidation State Of Soamentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, dry deposition velocities of semivolatile species have been shown to be significantly different for some species in winter (Jaeglé et al, 2017). Although in the last few decades there have been a number of wintertime studies of aerosols in Asia (e.g., Cao et al, 2003;Kim et al, 2017;Rengarajan et al, 2007Rengarajan et al, , 2011Takegawa et al, 2005;Xu et al, 2016;Zhang et al, 2015) and Europe (e.g., Bardouki et al, 2003;Castro et al, 1999;Crippa et al, 2013;Lanz et al, 2008;Louvaris et al, 2017;Viana et al, 2006), very few have been conducted in North America (e.g., Budisulistiorini et al, 2016;Öztürk et al, 2013;Song et al, 2001;Strader et al, 1999;Tan et al, 2002;Weimer et al, 2006;Xu et al, 2015). However, most of the North American studies were conducted at least a decade ago, and none were conducted in the northeastern United States (NE-US).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of OOA reported in urban environments varies greatly depending on the geographical location, but in general, accounts for approximately 50-80% of the total OA mass during the summer. In the winter, fewer studies have reported on measurements of urban OOA (Crippa et al, 2013;Kim et al, 2017;Öztürk et al, 2013;Pirjola et al, 2017;Zhang et al, 2015), showing fractions of OA mass between 20% and 70%.…”
Section: Introductionmentioning
confidence: 99%